Shallow-water Demospongiae (Porifera) from Sodwana Bay, iSimangaliso Wetland Park, South Africa - Samaai, Toufiek; Pillay, Ruwen; Janson, Liesl (Zootaxa, 2019)
33 species of shallow-water Demospongiae (Phylum Porifera) are described from Sodwana Bay, iSimangaliso Wetland Park, on the east coast of South Africa. Of the 33 species collected, 18 are redescribed from fresh material and 15 are new to science. Orders Clionaida, Poecilosclerida, Axinellida, Haplosclerida and Dictyoceratida are well represented in the collection with 4 to 6 species each, with the first three groups appearing to have the greatest diversity on the east coast of South Africa. The east coast of South Africa appears to have a high abundance of poecilosclerid and dictyoceratid sponges. The results of this study underscore the importance of poecilosclerid and dictyoceratid sponge fauna of the east coast of South Africa, in terms of the potential for the continued discovery of new species.